When the unification becomes a focal point of misunderstanding - Lalić, Gordana (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2021)
Although the acceleration of digitalisation is increasing the pressure to speed up and simplify procedures and adapt legislative drafting and decision making models, changes need to be approached gradually and thoughtfully. The methods of shaping the content of regulations or the basic concepts of how regulations are written have remained essentially the same for a long time. One should approach any changes to legal concepts carefully and look critically at the existing legislative procedure. The shorter life-cycle of legislation and improved technical possibilities tend to make changes to the traditional legislative drafting methods even where there is no need to do so. One should always ask themselves the following questions: can the legislative process be accelerated, and perhaps even more importantly – can it be improved?
Keywords: legislative drafting; references; digitalisation; EU v. national legislation; multilingualism; 5. Europäisches Symposium zur Verständlichkeit von Rechtsvorschriften